2022
DOI: 10.7554/elife.82094
|View full text |Cite
|
Sign up to set email alerts
|

A role for the centrosome in regulating the rate of neuronal efferocytosis by microglia in vivo

Abstract: During brain development, many newborn neurons undergo apoptosis and are engulfed by microglia, the tissue-resident phagocytes of the brain, in a process known as efferocytosis. A hallmark of microglia is their highly branched morphology characterized by the presence of numerous dynamic extensions that these cells use for scanning the brain parenchyma and engulfing unwanted material. The mechanisms driving branch formation and apoptotic cell engulfment in microglia are unclear. By taking a live-imaging approac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…However, the mechanism underlying this retrograde movement has not been clarified. In the zebrafish optic tectum, apoptotic neurons are removed by microglial phagocytosis, which is initiated by forming phagocytic cups without translocation of the cell body, similar to the phagocytic behavior of ramified microglia observed in the mouse SGZ (Möller et al, 2022). The experimental perturbation of the microtubule system disrupted the pattern of phagocytosis in zebrafish microglia.…”
Section: Multiple Modes Of Microglial Phagocytosis In Vivomentioning
confidence: 70%
“…However, the mechanism underlying this retrograde movement has not been clarified. In the zebrafish optic tectum, apoptotic neurons are removed by microglial phagocytosis, which is initiated by forming phagocytic cups without translocation of the cell body, similar to the phagocytic behavior of ramified microglia observed in the mouse SGZ (Möller et al, 2022). The experimental perturbation of the microtubule system disrupted the pattern of phagocytosis in zebrafish microglia.…”
Section: Multiple Modes Of Microglial Phagocytosis In Vivomentioning
confidence: 70%
“…Morphologically, they are highly spiky cells, closely resembling the microglia, which are the resident macrophages of the vertebrate CNS. 122,123 Furthermore, like the microglia, the Drosophila phagocytic glia appear to use their spiky, "filopodial" protrusions to reach out and grasp cellular debris (Figure 2). 78 While embryonic glial phagocytosis appears to be morphologically homogeneous, engulfment throughout embryogenesis can be far more diverse, as exhibited by the very dynamic and multifunctional macrophages.…”
Section: Phagocytes Exhibit Distinct Modes Of Engulfmentmentioning
confidence: 99%
“…They are embedded within a tightly packed tissue, where they are, unsurprisingly, immobile. Morphologically, they are highly spiky cells, closely resembling the microglia, which are the resident macrophages of the vertebrate CNS 122,123 . Furthermore, like the microglia, the Drosophila phagocytic glia appear to use their spiky, “filopodial” protrusions to reach out and grasp cellular debris (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Müller glia may actively sense and reach dying cells with cellular processes that then enclose around the target. In addition, given that we and others reported that microglia are the dominant phagocyte in the developing CNS (Blume et al, 2020; Casano et al, 2016; Mazaheri et al, 2014; Möller et al, 2022), there remains a strong possibility that interactions between microglia and other cell types such as the Müller glia occur during, and to facilitate, the clearance process. While early endosomal markers support active engulfment of dying cells by Müller glia in the absence of microglia (Thiel et al, 2022b), lysosomal fusion of such compartments upon engulfment within Müller glia has not been clearly demonstrated.…”
Section: Introductionmentioning
confidence: 95%